การพัฒนาอุปกรณ์เพื่อกำจัดฝุ่นละออง และมลพิษทางอากาศ - เสริมสุข รอดรังนก (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
Air pollution is one of the pressing problems in many countries including Thailand that must deal with the dust problems, especially small particles of 10 and 2.5 microns which cause the health hazard. These problems tend to expand and grow violent. Thus, this study aims to develop the air purifier using natural rubber filter to filter dust and adsorb carbon dioxide. The natural rubber filter with silica modified by amine is prepared to enhance the surface area and carbon dioxide adsorption capacity. There are 4 types of natural rubber filters used in this research such as unperforated rubber filter (A type), perforated rubber filter (B type), perforated rubber filter with unmodified silica (C type) and perforated rubber filter with modified silica (D type). From the experiment, the results show that the ability to adsorb PM2.5 dust and carbon dioxide arranges in descending order as follows: D > C > B > A with the PM2.5 reduction percentages of 61.02, 58.18, 52.38, 45.79 and the carbon dioxide reduction percentage of 41.42, 37.93, 31.19, 26.67, respectively. Finally, the D type-natural rubber filter is regenerated and it can be reused up to 3 cycles with the adsorption capacity of PM2.5 and carbon dioxide reduction by 23.77% and 27.75%, respectively.